2018
DOI: 10.6061/clinics/2018/e549s
|View full text |Cite
|
Sign up to set email alerts
|

Innate immunity and HPV: friends or foes

Abstract: Most human papillomavirus infections are readily cleared by the host immune response. However, in some individuals, human papillomavirus can establish a persistent infection. The persistence of high-risk human papillomavirus infection is the major risk factor for cervical cancer development. These viruses have developed mechanisms to evade the host immune system, which is an important step in persistence and, ultimately, in tumor development. Several cell types, receptors, transcription factors and inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 77 publications
0
25
0
Order By: Relevance
“…These factors include the chemokine CCL2 and the macrophage colony-stimulating factor (M-CSF), and several immunosuppressive modulators such as TGF-β, IL-10, IL-6, and PGE2 (141), which have been found to be upregulated in HPV-associated tumors. In addition to tumor cell-derived factors, T helper 2 (Th2) cytokines such as IL-4, IL-10, and IL-13 also promote the differentiation of TAMs, whereas Th1 cytokines have an inhibitory role (142). Interestingly, it has been suggested that the interaction between Th1 cells and TAMs can induce the repolarization of TAMs into M1 macrophages, an anti-tumor type of macrophage (143).…”
Section: Immune Evasion Of Hpv By Modulating the Immune Networkmentioning
confidence: 99%
“…These factors include the chemokine CCL2 and the macrophage colony-stimulating factor (M-CSF), and several immunosuppressive modulators such as TGF-β, IL-10, IL-6, and PGE2 (141), which have been found to be upregulated in HPV-associated tumors. In addition to tumor cell-derived factors, T helper 2 (Th2) cytokines such as IL-4, IL-10, and IL-13 also promote the differentiation of TAMs, whereas Th1 cytokines have an inhibitory role (142). Interestingly, it has been suggested that the interaction between Th1 cells and TAMs can induce the repolarization of TAMs into M1 macrophages, an anti-tumor type of macrophage (143).…”
Section: Immune Evasion Of Hpv By Modulating the Immune Networkmentioning
confidence: 99%
“…[14] Moreover, certain studies have shown that the persistence of HPV infection might be related to modulation of host immune responses by the virus itself. [15] Hence, persistent genital warts might have several underlying causes, and not every patient with persistent condyloma acuminata has defective immune system (like the present patient). The refractory genital warts of our patient showed a favorable response to treatment with IFN-γ.…”
Section: Discussionmentioning
confidence: 81%
“…While most HPV infections are cleared by the host immune response, a persistent HPV infection is established in some individuals by evading immune-surveillance and generating an anti-inflammatory microenvironment resulting in suppression of Natural Killer cell activity and antigen presentation. 47 49 In addition, HPV infection promotes T-helper cell type 2 and CD4+ Tregs phenotypes and reduces T-helper cell type 1 phenotype, leading to suppression of cellular and humoral immunity and contributes to HPV persistence. In this study, we demonstrated the presence of HR-HPV in the tissues of 20% of BC specimens which is consistent with previously published worldwide data.…”
Section: Discussionmentioning
confidence: 99%